The Influence of Annealing Process on Crystallinity and Structural Properties of Cotton/Spandex Fabric - Pervez, Md. Nahid; Talukder, Md. Eman; Kanti Datta, Manoj; Mia, Md Shipan; Zaman, Ashaduz; Khan, Meer Md Rasel; Cai, Yingjie; Lin, Lina (MATEC web of conferences, 2017)
This research aims to elucidate the crystallinity, structural and mechanical properties of cotton/spandex knitted fabric after conducting heat setting i.e., annealing process with optimized condition for the first time. Experimental results disclosed that, crystallinity index (CI) (%) of heat-treated cotton/spandex were increased with increased temperature and also mechanical properties i.e., tensile strength was improved as the temperature rose from 120 to 140°C and decreased with augmenting temperature ranges, which is in good agreement with the findings of CI % through X-ray diffraction (XRD) patterns. The attendance of cellulose dehydration was further confirmed by Fourier transform infrared (FT-IR) spectra in order to observe the structural integrity.